Consumption-Related Health Education Inequality in COVID-19: A Cross-Sectional Study in China - You, Jialu; Zhang, Jinhua; Li, Ze (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic influences various aspects of society, especially for people with low socioeconomic status. Health knowledge has been proven to be a critical strategy in preventing a pandemic. However, the socioeconomic characteristic may limit undertaking health knowledge among low socioeconomic status groups. This study explores spending-related health knowledge inequality and the majority contributions variable across China during COVID-19. Methods: The 2020 China COVID-19 Survey is a cross-sectional study in China, based on an anonymous online survey from 3,715 samples in 187 cities. Employ machine study methods to assess the sociodemographic factors, including household spending, education, and income, health status, associated with health knowledge during the pandemic. Concentration Index (CI) and Horizontal Index (HI) were used to measure spending-related inequalities in health knowledge, respectively. Moreover, Wagstaff decomposition analysis was employed to identify the other socioeconomic contributors to health knowledge inequality. Results: The result indicates that participants with more education, better income, positively spending preference undertake higher health knowledge about COVID-19. The CI and HI of spending-health knowledge inequality are 0.0321(P<0.0001) and 0.0416(p<0.0001), respectively, which indicates that health knowledge concertation on wealth groups. We adapt Lasso regression to solve the issues about omit variables. In terms of another socioeconomic characteristic, Annuals Income was also the major contributor to health knowledge inequalities, accounting for 27.1% (P<0.0001). The decomposing also suggests that education, health status, identification residence, and medical health insurance contribute to health knowledge inequality. Conclusions: Household spending preference, annual income, rural and urban disparity, health medical insurance shortage are critical drivers of health knowledge. The government should pay more attention to promoting health knowledge, and healthcare subside policy among vulnerable people. Significantly to improve awareness of undertaking health knowledge with lower education, rural residential, to enhance confidence about economic recovery and life after COVID-19.